Alpha-2-Macroglobulin Is an Important Progressive Inhibitor of Thrombin in Neonatal and Infant Plasma - Schmidt, Barbara; Mitchell, Lesley; Ofosu, Frederick A; Andrew, Maureen (Thrombosis and Haemostasis, 1989)
Antithrombin III (ATIII) is the main inhibitor of thrombin in adult plasma; α2-macroglobulin (α2M) and heparin cofactor II (HCII) are of lesser importance. The relative contributions of these inhibitors to the inactivation of thrombin may differ during the neonatal period and infancy, when plasma concentrations of α2M are about twice as high as those of ATIII. We therefore compared the relative importance of these anti-proteases for the inhibition of 125I-thrombin in defibrinated pooled adult and neonatal plasma. Observations were also made in pooled plasma of 6 months old infants. 125I-thrombin-inhibitor complexes were quantitated after SDS-PAGE and autoradiography by scanning densitometry. Thrombin (2.5 NIH U/ml) was inhibited more slowly in neonatal than in adult plasma. However, both plasmas inhibited 88% of the added thrombin by 5 minutes. α2M inhibited consistently a larger fraction of thrombin in neonatal than in adult plasma. Consequently, the ratio of thrombin bound to ATIII over thrombin bound to α2M was significantly lower in neonatal (<2.5) than in adult plasma (>4.5; p <0.0001). In infant plasma, this ratio was <2.0. Upon addition of therapeutic amounts of heparin (0.4 U/ml), differences between the contributions of ATIII and α2M to the inhibition of thrombin were no longer apparent, as over 90% of complexed thrombin was bound to ATIII in heparinized plasmas of all age groups. We conclude that α2M is an important progressive inhibitor of thrombin in young infants. This finding may explain why healthy newborns rarely suffer from thrombosis, despite their low plasma ATIII levels.
Keywords: Alpha-2-macroglobulin; Antithrombin III; Newborn